Marijuana: Current Concepts† - Greydanus, Donald; Hawver, Elizabeth K.; Greydanus, Megan M.; Merrick, Joav (Frontiers in Public Health, 2013)
Marijuana (cannabis) remains a controversial drug in the 21st century. This paper considers current research on use of Cannabis sativa and its constituents such as the cannabinoids. Topics reviewed include prevalence of cannabis use, other drugs consumed with pot, the endocannabinoid system, use of medicinal marijuana, medical adverse effects of cannabis, and psychiatric adverse effects of cannabis use. Treatment of cannabis withdrawal and dependence is difficult and remains mainly based on psychological therapy; current research on pharmacologic management of problems related to cannabis consumption is also considered. The potential role of specific cannabinoids for medical benefit will be revealed as the 21st century matures. However, potential dangerous adverse effects from smoking marijuana are well known and should be clearly taught to a public often confused by a media-driven, though false message and promise of benign pot consumption.